Outcome-Based Education, E-Learning, and Student Satisfaction: Evidence from Indonesia and Thailand - Ahmad Salim; Ibrahim Narongraksakhet; Aida Hayani; Kana Safrina Rouzi; Mufida Awalia Putri; Aris Hassama; Ahmad Anis Abdullah (Jurnal Ilmiah Peuradeun, 2026)
The implementation of the Outcome-Based Education (OBE) curriculum in Southeast Asia, particularly in Indonesia and Thailand, is relatively new; therefore, it is interesting to research students' responses to its implementation. This research aims to determine students' responses to the implementation of the OBE supported by E-Learning as a form of evaluation of the ongoing learning process. The subjects of this research were 250 students at the Faculty of Tarbiyah and Teacher Training at Alma Ata University (UAA), Indonesia, and 250 students at the Islamic College at Prince of Songkla University (PSU), Thailand. This research hypothesizes that the implementation of the OBE curriculum supported by E-Learning at both universities has a significant influence on student satisfaction with learning. This research uses quantitative methods with a quasi-experimental research design. Based on the research results obtained, there was an increase in average student satisfaction before and after the implementation of the OBE Curriculum, supported by E-Learning, at the two universities. This can be seen from the results of the Independent Samples t Test with sig. P-value <0.05. The OBE Curriculum, supported by E-Learning with a blended learning model, is very suitable for implementation at universities as a form of learning revolution in the digital era.